Oh what a slaughter massacres in the American West, 1846-1890 - McMurtry, Larry 1936-2021 (Simon & Schuster, 2005)
A history of the bloody massacres that marked--and marred--the settling of the American West in the nineteenth century, and which still provoke immense controversy today. Here are the true stories of the massacres at Sacramento River, Mountain Meadows, Sand Creek, Marias River, Camp Grant, and Wounded Knee, among others. These massacres involved Americans killing Indians, Indians killing Americans, and, in one case, Mormons slaughtering a party of settlers. McMurtry's descriptions recall their full horror, and the deep, constant apprehension and dread endured by both pioneers and Indians. By modern standards the death tolls were small--Little Big Horn in 1876 was the only encounter to involve more than 200 dead--yet in the thinly populated West of that time, the violent extinction of a hundred people had a colossal impact. At the sites today, the taint is still powerful enough to affect locals who happen to live nearby.--From publisher description.
Includes bibliographical references (p. [163]-165) and index
Keywords: Geschichte 1800-1900; Geschichte; Indianer; Indians of North America -- Wars -- West (U.S.); Indians of North America -- West (U.S.) -- History -- 19th century; Massacres -- West (U.S.) -- History -- 19th century